The Role of Islamic Education In Student Organizations to Realize Human Resources In The Review of Higher Education Law Perspectives - Ferry Irawan Febriansyah; Achyat Daroini; Widowati Widowati (Al-Hayat: Journal of Islamic Education, 2019)
Education, mainly Islamic based learning, can be found in formal schools, non-formal and informal institutions. A person can freely choose which path to use as a way to take talent and potential in him; even when making formal education, even an individual has the right to participate in non-formal education activities. One of the most appropriate places to forge one's abilities is the campus. It is undeniable that students are one of Indonesia's most influential human resources and are also the next generation of nation-building. Therefore the cadre regeneration function is the most basic. As a generation that must carry out the role of regeneration for the sake of the realisation of the good and happiness of the people, nation and country in the future. Therefore education is needed to help towards the better. Islamic culture has a vital role in the education model that exists in Indonesia. Islamic education is used to improve human morals in a better direction with Islamic methods. It can be observed that student organisations within the campus need a strong foundation to improve their quality in faith and loyalty that has both physical and spiritual intelligence. It is here that the need for Islamic education in helping them is better by the mandate of the national education law. Pendidikan, terutama pembelajaran berbasis Islam, dapat ditemukan di sekolah formal, lembaga non-formal dan informal. Seseorang dapat dengan bebas memilih jalan mana yang akan digunakan sebagai cara untuk mengambil bakat dan potensi dalam dirinya; bahkan ketika membuat pendidikan formal, bahkan seorang individu memiliki hak untuk berpartisipasi dalam kegiatan pendidikan non-formal. Salah satu tempat paling tepat untuk menempa kemampuan seseorang adalah kampus. Tidak dapat dipungkiri bahwa siswa adalah salah satu sumber daya manusia Indonesia yang paling berpengaruh dan juga merupakan generasi penerus bangsa. Karena itu fungsi regenerasi kader adalah yang paling mendasar. Sebagai generasi yang harus menjalankan peran regenerasi demi terwujudnya kebaikan dan kebahagiaan rakyat, bangsa dan negara di masa depan. Oleh karena itu diperlukan pendidikan untuk membantu menuju yang lebih baik. Budaya Islam memiliki peran penting dalam model pendidikan yang ada di Indonesia. Pendidikan Islam digunakan untuk meningkatkan moral manusia ke arah yang lebih baik dengan metode Islam. Dapat diamati bahwa organisasi mahasiswa di dalam kampus membutuhkan dasar yang kuat untuk meningkatkan kualitas mereka dalam iman dan kesetiaan yang memiliki kecerdasan fisik dan spiritual. Di sinilah perlunya pendidikan Islam dalam membantu mereka lebih baik dengan mandat hukum pendidikan nasional.